Study of Gel Growth Cobalt (II) Oxalate Crystals as Precursor of Co3O4 Nano Particles - Yuniar Ponco Prananto; Mohammad Misbah Khunur; Dini Tri Wahyuni; Rizky Arief Shobirin; Yoga Rizky Nata; Efiria Riskah (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Crystal growth of cobalt (II) oxalate in silica gel at room temperature as precursor of Co3O4 nano particles has been studied. Specifically, this project is focusing on the use of two different reaction tube types toward crystallization of cobalt (II) oxalate in gel. The gel was prepared at pH 5 by reacting sodium metasilicate solution with dilute nitric acid (for U-tube) and oxalic acid (for straight tube), with gelling time of 4 days and crystal growth time of 8 (for straight tube) and 12 (for U-tube) weeks. Result shows that pink crystalline powder was directly formed using straight tube method. The use of different solvents in straight tube method affects crystallization and could delay direct precipitation of the product. In contrast, bigger and better shape of red block crystal was yielded from U-tube method; however, longer growth time was needed. FTIR studies suggest that both growth method produces identical compound of hydrated cobalt (II) oxalate. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)